Megacostalism and the pandemic: Developing a megacostal theology of care beyond COVID-19 - Kgatle, Mookgo Solomon (Verbum et ecclesia, 2024)
Megacostalism is a concept developed here to refer to the growing trend of mega Pentecostal churches in Africa. The mega Pentecostal churches are popular in the United States of America with leading pastors such as T.D. Jakes, Creflo Dollar, Joel Osteen, and so forth. There is an interesting growing trend of this type of churches in Africa particularly in West Africa in countries such as Nigeria and Ghana. There has also been a development of mega Pentecostal churches in South Africa after 1994. This article assesses this phenomenon by paying attention to how such churches dealt with the challenges of coronavirus disease 2019 (COVID-19) as opposed to smaller churches. The study will use a case study method to assess the COVID-19 experiences in churches such as the Rhema Bible Church in Randburg, Christian Revival Church and Doxa Deo. This article will attempt to address these research questions through a conceptualisation of megacostalism. In addition, the study will look at how different mega Pentecostal churches dealt with COVID-19 to develop a proper megacostal theology of care beyond COVID-19. Intradisciplinary and/or interdisciplinary implications: This article is interdisciplinary between theology and the health sciences among the mega Pentecostal churches in the context of Pentecostalism. The study makes an important contribution to both the study of theology and epidemiology in the understanding of challenges posed by pandemics such as COVID-19 and how to address such challenges through a theology of care.